Two Novel EGFP Insertion Alleles Reveal Unique Aspects of Pax2 Function in Embryonic and Adult Kidneys - Soofi, Abdul (2012)
The Pax2 gene encodes a DNA binding protein with multiple functions in the developing intermediate mesoderm and urogenital tract. Loss of Pax2 in mice results in the complete absence of kidneys, ureters, and sex specific epithelial structures derived from the intermediate mesoderm in both males and females. In this report, we describe two new alleles of Pax2 created by inserting the Enhanced Green Fluorescent Protein coding region into the 5′ untranslated leader sequence. One allele is a hypomorph that generates less protein and exhibits structural defects in kidneys and ureters upon homozygosity. A second allele is a true null that can be used to image Pax2 expressing cells in a mutant background. Organ culture and embryo analyses point to a loss of epithelial cell polarity and increased mobility in cells that have deleted Pax2 function. These experiments provide new insight into the role of Pax2 protein levels in determining correct renal architecture and cell fate. These new Pax2 alleles are valuable genetic reagents for in vivo studies of urogenital development.